Quartz grainsize evolution during dynamic recrystallization across a natural shear zone boundary. (April 2018) - Xia, Haoran; Platt, John P.
Abstract: Although it is widely accepted that grainsize reduction by dynamic recrystallization can lead to strain localization, the details of the grainsize evolution during dynamic recrystallization remain unclear. We investigated the bulge size and grainsizes of quartz at approximately the initiation and the completion stages of bulging recrystallization across the upper boundary of a 500 m thick mylonite zone above the Vincent fault in the San Gabriel Mountains, southern California. Within uncertainty, the average bulge size of quartz, 4.7 ± 1.5 μm, is the same as the recrystallized grainsize, 4.5 ± 1.5 μm, at the incipient stage of dynamic recrystallization, and also the same within uncertainties as the recrystallized grainsize when dynamic recrystallization is largely complete, 4.7 ± 1.3 μm. These observations indicate that the recrystallized grainsize is controlled by the nucleation process and does not change afterwards. It is also consistent with the experimental finding that the quartz recrystallized grainsize paleopiezometer is independent of temperature. Highlights: Quartz grain-boundary bulge size is the same as the BLG-recrystallized grain size. The recrystallized grain size is independent of the amount of recrystallization. Nucleation-and-growth models for dynamic recrystallization are not supported.